The twentieth century in poetry : a critical survey - Childs, Peter, 1962- (Routledge, 1999)
This text examines both "English" poetry through the events of the 20th century and British history through its representations in recent poetry. It builds a narrative not of poetry in the 20th century but of the 20th century in poetry. A high proportion of literature courses include an exploration of the issues of gender, ethnicity, theory, nationality, politics and social class. But until now most teaching has focused on the novel as the most useful way of raising these issues. Peter Childs demonstrates that all poetry is historically produced and consumed and is part of our understanding of society and identity. This student-friendly critical survey includes chapters on: the Georgians; First World War poetry; Eliot; Yeats; the thirties; post-war poetry; contemporary anthologies; women's poetry; and Northern Irish and black British poets. Placing literature in a wider social context, this book examines the way in which recent theory has questioned divisions between "history" and literature, between "text" and "event", between society and the individual